Association and Risk of Axial Spondyloarthritis of Scoliosis Patients: A Database Study. Issue 5 (1st March 2022) - Yong, Jocelyn Huan; Hong, Jia-Pei; Lee, Yu-Hao; Huang, Chi-Chang; Huang, Shih-Wei; Lin, Hui-Wen
Abstract : Study Design: Retrospective longitudinal cohort study. Objective: To investigate the incidence and risk of axial spondyloarthritis (axSpA) in patients with scoliosis in Taiwan. Summary of Background Data: Scoliosis and axSpA causes back pain which reduces quality of life in many patients. Both scoliosis and axSpA had attracted numerous research attention, but the association between the two was hardly known. Methods: In this retrospective study, the data of 25, 566 patients were obtained from Taiwan's National Health Insurance Research Database. We identified patients diagnosed with scoliosis and included them in the study cohort. We included age- and sex-matched patients without scoliosis in the control cohort. The total follow-up period was 7 years. Cox proportional hazards models were used to analyze the retrieved data. Hazard ratios (HRs) and adjusted HRs were calculated. Results: The study and control cohorts included 4261 and 21, 305 patients, respectively. The incidences of axSpA were 141 and 46 per 100, 000 person-years in the study and control cohorts, respectively. The crude HRs and adjusted HRs for patients with scoliosis were 2.98 (95% confidence interval, 1.87–4.73; P  < 0.001) and 2.78 (95% confidence interval, 1.74–4.43; P  < 0.001), respectively. The prevalence of comorbidities such as chronic obstructive pulmonary disease, osteoporosis, depression, autoimmune diseases (rheumatoid arthritis and systemic lupus erythematosus), and thyroid disease was significantly higher in the study cohort. Conclusion: Our findings indicate an association between scoliosis and axSpA. Additional studies should be performed to explain this phenomenon. Level of Evidence: 3 Abstract : This study explored the incidence of axSpA in scoliosis patient using the Taiwan's National Health Insurance Research Database. The incidence of AxSpA is three times higher in scoliosis patients. Higher prevalence of comorbidities such as COPD, osteoporosis, depression, autoimmune diseases, and thyroid disease was also noted in the study cohort.